A Matrix Approach to the Depreciation Lapse Schedule Preparation. - Liao, Mawsen (The Accounting Review, 1976)
Abstract Accountants frequently prepare depreciation lapse schedules showing depreciation expense by year for each depreciable asset. Such schedules are used in providing financial data for management planning functions, such as tax planning, cash flow budgets and forecasting financial statements. The traditional method becomes impractical, inconvenient and expensive when a schedule contains a large number of items and years. The purpose of this article is to introduce a practical application of the matrix method for the preparation of depreciation lapse schedules. The depreciation rate is determined by the depreciation policy. The matrix approach also provides an efficient framework for computerizing the calculation process. A depreciation lapse schedule, when prepared on the company's year basis, provides information for tax planning, budgeting and forecasting as well as for financial accounting and reporting. The matrix method when computerized provides a convenient and efficient framework for performing the necessary computations.